EFFECTIVE STRATAGIES FOR TEACHING ENGLISH PRONUNCIATION TO UZBEK LEARNES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Teaching English pronunciation to non-native speakers is a crucial component of language learning, as accurate pronunciation significantly affects communication and comprehension. Uzbek learners often face specific challenges in acquiring English pronunciation due to differences between the phonetic systems of Uzbek and English. These challenges include difficulties in producing certain consonant clusters, distinguishing between vowel sounds that do not exist in Uzbek, and mastering word stress and intonation patterns. This paper explores effective strategies that English language teachers can employ to address these challenges and improve learners’ pronunciation skills.